PENGARUH KOMPETENSI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. JASA SWADAYA UTAMA - Setiarlan, Agus; Ahmadun; Nurminingsih; Asim (Transpublika Publisher, 2021)
This study aims to examine the effect of competence and transformational leadership on employee work productivity at PT Jasa Swadaya Utama. This research is quantitative descriptive research. The study population was 98 people. The data analysis technique used is descriptive statistical analysis, while the method of analysis used in this study was PLS (Partial Least Square) using SmartPLS version 3.0.m3. The results showed that competence has a positive and significant effect on work productivity and competence has a positive and significant effect on transformational leadership. Meanwhile, transformational leadership has a positive and significant effect on work productivity. Simultaneous testing of the results of data analysis shows that competence and transformational leadership have a positive and significant effect on work productivity while the rest is influenced by other factors. Keyword: Work Productivity, Competence and Transformational Leadership